تأثیر النظام الضریبي لدول المغرب على قرارات الاستثمار – دراسة مقارنة لدول تونس، الجزائر والمغرب- - KHALDI Aissam; GHARBI Hamza (université msila, 2022)
The present article aims to survey the impact of Tax System of countries on the investment decision, through surveying convergent Tax System of some Maghreb countries under Francophone system and other systems that have an impact on investment depending on a set of previous studies and some documents, laws and indicators, where the study concluded that the Tax System has a significant impact in making investment decision
Keywords: Investment Decision Making ; Fiscal System ; Fiscal Privilege ; Fiscal Obligation ; System Effect.